2008
DOI: 10.1088/0031-9155/53/14/005
|View full text |Cite
|
Sign up to set email alerts
|

Estimated limits of IMRT dose escalation using varied planning target volume margins

Abstract: To estimate the limits of dose escalation for prostate cancer as a function of planning target volume (PTV) margins, the maximum achievable dose (MAD) was determined through iterative plan optimizations from data sets of 18 patients until the dose constraints for rectum, bladder and PTV could no longer be met. PTV margins of 10, 5 and 3 mm yielded a mean MAD of 83.0 Gy (range, 73.8-108.0 Gy), 113.1 Gy (range, 90.0-151.2 Gy) and 135.9 Gy (range, 102.6-189.0 Gy), respectively. All comparisons of MAD among margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This will facilitate dose escalation and better tumour control. 17,18 It is expected that the magnitudes of the CTV/PTV margin will follow a similar pattern as the set-up deviations obtained from this study.…”
Section: Implications On Estimation Of Clinical Target Volume-planninsupporting
confidence: 71%
“…This will facilitate dose escalation and better tumour control. 17,18 It is expected that the magnitudes of the CTV/PTV margin will follow a similar pattern as the set-up deviations obtained from this study.…”
Section: Implications On Estimation Of Clinical Target Volume-planninsupporting
confidence: 71%
“…However, to limit normal tissue toxicity, treatment margins have to be decreased. ( 2 , 3 ) In order to reduce treatment margin, the issue of organ motion needed to be addressed, so that the location of the target could be accurately determined during treatment. Target motion, for example, can cause a geometric miss in dose delivery; (4) hence, accurate radiation therapy requires knowledge of the exact location of the tumor at the time of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer radiotherapy, the degree of overlap between the rectum and PTV has been shown to be the most important predictor of benefit from IMRT as compared to 3D-CRT [1,2,3], determines the limits of dose escalation possible [6,24], and can predict the degree of rectal sparing after hydrogel injection [18]. Similarly, in this study we have shown that the degree of overlap between PTV and bladder or rectum adversely effects sparing of that organ not only in the high-dose region of the dose-volume histogram, but also in the low-dose region as well.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric-modulated arc therapy (VMAT), the next generation of IMRT, allows for variation in the dose rate, speed of gantry rotation, and multi-leaf positions during rotation of the gantry in a full 360 degree arc, and has been shown to yield even further OAR sparing as compared to fixed-beam IMRT in prostate cancer [4,5]. However, regardless of the treatment delivery technique, if a large amount of overlap between PTV and OAR exist it may be physically impossible to achieve uniform coverage of the PTV with the prescription dose while also adequately sparing that OAR [6]. …”
Section: Introductionmentioning
confidence: 99%